Review of The Business of Slavery and the Rise of American Capitalism, 1815–1860 by Calvin Schermerhorn and The Half Has Never Been Told: Slavery and the Making of American Capitalism by Edward E. Baptist - Engerman, Stanley L. (Journal of Economic Literature, 2017)
The two books being reviewed are concerned with the importance of slavery in the antebellum US South for the economic development of the Northern states. One (Schermerhorn) deals primarily with Southern financial arrangements facilitating the sales of slaves and cotton. The other (Baptist) presents a broader picture of masters' treatment of slaves, as well as how the incomes of slaveowners spurred the demand for Northern industrial production. The review argues that both books overstate the importance of slavery and cotton production for US economic growth. (JEL J15, N11, N31, N51, P16)